Union framing of gender equality and the elusive potential of equality bargaining in a difficult climate. (September 2021) - Kirton, Gill
This article explores why equality bargaining appears to remain underdeveloped despite its widely acknowledged potential for tackling workplace inequalities. The concept from social movement theory of 'framing' is utilised to assess the prospects of moving from 'where we are'. Findings from a study of UK-based union equality actors discuss unceasing efforts on their part to shift equality from the margins to the centre of union bargaining activity. As regards 'where to next', Equality Officers' strategic deployment of the longstanding union equality frames of 'women's issues' and 'gender mainstreaming' challenges taken-for-granted social practices within unions, offering some optimism that creative strategies can help to inject equality frames into traditional union frames, thus producing an expanded and inclusive notion of union solidarity. However, this framing activity occurs within existing opportunity structures with all their facilitative and inhibitive factors, including resistant union officers and reps, which previous research has highlighted. Therefore, a less optimistic vision is that the weight of union tradition that has long privileged male interests, combined with contemporary hostile bargaining conditions, are just too great for equality bargaining to reach its full potential.